2016
DOI: 10.3847/0004-637x/825/1/39
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Splashback Radius and Halo Assembly Bias of Massive Galaxy Clusters

Abstract: We show that the projected number density profiles of SDSS photometric galaxies around galaxy clusters displays strong evidence for the splashback radius, a sharp halo edge corresponding to the location of the first orbital apocenter of satellite galaxies after their infall. We split the clusters into two subsamples with different mean projected radial distances of their members, R mem , at fixed richness and redshift, and show that the sample with smaller R mem has a smaller ratio of the splashback radius to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
273
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(299 citation statements)
references
References 69 publications
23
273
2
1
Order By: Relevance
“…It refers to the dark matter halo assembly bias (Gao et al 2005;Croton et al 2007), whose inference requires the identification of isolated halo samples. Supporting evidence has been reported by Miyatake et al (2016) in massive clusters, and later expanded by More et al (2016).…”
Section: Introductionsupporting
confidence: 59%
“…It refers to the dark matter halo assembly bias (Gao et al 2005;Croton et al 2007), whose inference requires the identification of isolated halo samples. Supporting evidence has been reported by Miyatake et al (2016) in massive clusters, and later expanded by More et al (2016).…”
Section: Introductionsupporting
confidence: 59%
“…More et al (2015) adopted the definition of R sp as the radius where the density profile reaches its steepest slope and investigated its dependence on mass accretion rate and redshift. Finally, More et al (2016, see also Adhikari et al 2016and Baxter et al 2017) detected a sharp drop in the stacked density …”
mentioning
confidence: 78%
“…The measurement of R sp performed by More et al (2016) and confirmed by Baxter et al (2017) indicates a surprisingly small splashback radius, namely, R sp /R 200m = 0.837 ± 0.031 for a cluster sample with ν = 2.4 at z = 0.24. While we cannot directly measure the mass accretion rate of the clusters, Figure 3 clearly shows that the theoretically expected value is higher.…”
Section: Compatibility With Observationsmentioning
confidence: 89%
“…However, the Einasto model is sufficiently flexible that even without such a truncation, it can still reproduce a splashbacklike steepening in the outer halo profile. Consequently, the evidence for splashback quantified either with a Δχ 2 (as in More et al 2016) or with a Bayesian evidence ratio (as in B17) can be misleadingly low, even when there is significant steeping of the outer halo profile. This problem becomes more severe when additional flexibility is introduced to the model to account for halo mis-centering, for example.…”
Section: Introductionmentioning
confidence: 99%